Production of Fish Hydrolysates Protein From Waste of Fish Carp (Cyprinus Carpio) by Enzymatic Hydrolysis - Saputra, Dede; Nurhayati, Tati (ComTech: Computer, Mathematics and Engineering Applications, 2016)
Fish Protein Hydrolysates (FPH) is the mixed products of polypeptide, dipeptides, and amino acid. It can be produced from materials that contained of protein by acid reaction, base reaction or enzymatic hydrolysis. The objectives of this study were to study the production of FPH from fish carp meat at post rigor phase and viscera by enzymatic hydrolysis, to determine the specific activity of papain enzyme, and to determine the solubility of FPH. Capacity of fish hydrolyzing can be identified by analyzing the content of dissolved total nitrogen (NTT) compared with nitrogen total ingredient (NTB) in order to get the value of total soluble nitrogen/total nitrogen material (NTT/NTB). The hydrolysis processes were carried out in 0,26% (w/v) papain, 60 ?C for 3 hours. The result showed that the specific activity of papain enzyme was about 3.28 U/mg. Solubility of FPH by comparing NTT/NTB was about 0.29% (fish meat) and 0.40% (fish viscera). Proximate test of protein content of fish meat was 18.34 ± 0.04 (g/100 g); while viscera was about 0.95±0.04 (g/100 g). The result indicated that product waste of fish carp had potential as a major of source of FPH.